Dimmersion for Industrial Design (2024)
Purpose – The purpose of this project, titled "Dimmersion," is to provide an immersive experience that allows high school students in Colombia (grades 8 to 11) to explore the Industrial Design program in a new and challenging way. The aim is to spark interest in the field and develop relevant skills through a series of dynamic and interactive activities. Design/methodology/approach - The project features four stations representing key design competencies: Prototyping, Sketching, Creative Thinking, and Social Responsibility. Each station includes 30 task cards with simple, measurable 5-minute group challenges. Motivation levels are assessed before and after the experience using the Termmersion tool. Findings – The initial trial at ICESI Interactive was successful, engaging around 100 participants. While logistical issues like participant numbers and rule clarity were noted, they were managed effectively. The project proved scalable and effective in engaging students. Practical implications – Dimmersion offers a practical, scalable method to introduce students to Industrial Design, helping them develop essential skills and increasing interest in the field. It can be adapted to various educational contexts and group sizes. Originality/Value – Dimmersion uniquely combines hands-on activities with dynamic interactions, bridging theoretical knowledge and practical application. Tools like the Termmersion for motivation measurement add novelty to the educational experience. Keywords – Industrial Design, Immersive Experience, High School Education, Prototyping, Sketching, Creative Thinking, Social Responsibility, Educational Games.